2017
DOI: 10.1136/bmjgh-2017-000368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose versus higher-dose antenatal iron supplementation on child health outcomes at 36 months of age in Viet Nam: longitudinal follow-up of a cluster randomised controlled trial

Abstract: IntroductionIntermittent iron-folic acid supplementation (IFA) is currently recommended for pregnant women in populations where anaemia prevalence among pregnant women is <20% or if daily iron is not acceptable. The effect of providing lower doses of antenatal elemental iron through intermittent regimes on longer-term health outcomes in childhood is unclear.MethodsA prospective cohort study conducted between May 2012 and May 2014 in Viet Nam among children of 36 months of age, born to women previously enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“… 44 In a follow-up cohort study of the infants born to women in the trial, we found that lower dose antenatal iron supplementation led to impaired growth (Adjusted MD in HAZ were –0.14 (95% CI –0.28 to –0.01) and motor development (MD –2.07, 95% CI –4.11 to –0.03) in children at 3 years of age. 45 …”
Section: Introductionmentioning
confidence: 99%
“… 44 In a follow-up cohort study of the infants born to women in the trial, we found that lower dose antenatal iron supplementation led to impaired growth (Adjusted MD in HAZ were –0.14 (95% CI –0.28 to –0.01) and motor development (MD –2.07, 95% CI –4.11 to –0.03) in children at 3 years of age. 45 …”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence from case–control studies that iron deficient children (assessed in early childhood) perform worse in both mental development tests and motor development tests compared with iron‐replete children . Some preventive trials with iron supplementation favor a beneficial effect of iron on motor development . Despite heterogeneity between studies, meta‐analyses indicate that antenatal micronutrient supplementation is beneficial for fluid intelligence and that especially iron supplementation is beneficial for a range of cognitive outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…15 Some preventive trials with iron supplementation favor a beneficial effect of iron on motor development. [24][25][26][27] Despite heterogeneity between studies, meta-analyses indicate that antenatal micronutrient supplementation is beneficial for fluid intelligence and that especially iron supplementation is beneficial for a range of cognitive outcomes. 28 Results from newer and larger randomized trials will update evidence on short-term effects of antenatal iron supplementation on cognitive, mental, and motor development.…”
Section: Discussionmentioning
confidence: 99%
“…These MCID thresholds have previously been used in the sample size calculations of several MNCH trials. 25,26,27,28,29,30,31,32,33,34…”
Section: Methodsmentioning
confidence: 99%